Modelarea cuiburilor derivaționale ale verbelor emotive în limba română - Czarnecki, Szymon (Studia Romanica Posnaniensia, 2023)
The present paper aims to model derivational networks (nests) of emotive verbs in Romanian, on the basis of the semantic-structural types of derivatives. First, we define the most important notions of the nest derivatology, we introduce the notion of derivational nest modelling and of semantic-structural types of derivatives, and describe the principles of the analysis. After that, the derivational nests of selected verbs and their formal-semantic analysis are presented, with semantic and formal aspects in the commentary after each nest. At the end, the matrix of models resulting from the juxtaposition of all nest models and the conclusions from the research are presented.